Optimization of sustainable concrete characteristics incorporating palm oil clinker and nano-palm oil fuel ash using response surface methodology - Hamada, Hussein Mahmood; Attar, Alyaa; Shi, Jinyan; Fadzil, Mat Yahaya; Al Jawahery, Mohammed; Yousif, Salim (Elsevier Ltd, 2023)
The production of concrete by replacing cement and aggregates with biomass materials is a low-carbon footprint and low-cost approach. In this study, the influences of nano-palm oil fuel ash (NPOFA) and palm oil clinker (POC) partially replaced instead of cement (0, 15% and 30%) and coarse aggregate (0, 50%, 100%) into sustainable concrete on workability and compressive strength are investigated using response surface methodology (RSM) methods. The RSM forecasting has presented satisfactory outcomes in optimizing the quantity of POC and NPOFA in the production of concrete with acceptable strength. The peak compressive strength is achieved for the mixture containing 0% POC and 15% NPOFA, and the mixture containing 100% POC and 30% NPOFA has the lowest compressive strength. The optimum condition is successfully predicted using RSM. The use of NPOFA binder enhances the workability and compressive strength of concrete material, in addition to enhancing the sustainability of the concrete industry. Meanwhile, the results of economic and environmental assessments also show that the addition of NPOFA and POC significantly reduces the cost and carbon emissions of concrete, and the effect of NPOFA is even more pronounced. This method might result in the noteworthy consumption of POC and NPOFA in the production of concrete and assist in achieving environmental sustainability by reducing the agricultural and industrial waste by-products.